(untitled) (Global Journal of Human-Social Science, 2013)
Expressive creative encounters ECE are designed as spaces for the subjects to express and interpret their emotions in the context of social research The expressiveness of the social subjects has always been a controversial issue for social sciences because nobody can live-within-the-other But the development and improvement of qualitative social research strategies incorporating the expressiveness capture technologies in a progressive yet steady way have been able to bridge the gap between what the researcher sees and what the subject expresses In this work creativity is taken as a starting point to produce expressive experiences where individuals share and interpret both with the researcher and with others in particular social conditions of existence their sensations and emotions